Frequency and Risk Profiles Associated with Antenatal Anxiety and Depression in Middle Socioeconomic Women - Syeda Rabia; Uzma Nusrat; Sarah Qazi (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To  determine the frequency of antenatal anxiety and depression and its risk profile including demographic, psychosocial and obstetric risk factors, in middle socioeconomic women. Methods: A cross-sectional study was carried out at two private hospital centres of Karachi, over a pe-    riod of five months from October 2016 to March 2017. A questionnaire (age, education, parity, socio- economic status, employment) and the Hospital Anxiety and Depression Scale (HADS) were the tools    used to gather required information from pregnant women. Data collected was entered in SPSS 16  software. Descriptive statistics were used  to  calculate  frequency  and  mean  values.  Logistic  regres-  sion both binary and multinomial was performed to identify significant predictors of anxiety and de- pression. Results: Our study showed that out of 520 pregnant women, 130 (25%) women had anxiety, whereas 220 (42.3%) had depression. The mean  age  of  women  was  26.9  ±  4.198  years.  The  range  being  from 18 years to 35 years. Significant risk factors among anxiety group were: working woman; 30.8% (p-value=0.000, OR=0.286), domestic violence; 84.6%  (p-value=0.000,  OR=2.8),  difficult  relationship  with in-laws;  84.6%  (p-value=0.000,  OR=12.375),  sleep  disturbance;  76.9%  (p-value=0.000,  OR=9.667), primigravida; 23% (p-value=0.000, OR=2.576) and unplanned pregnancy; 23.1% (p- value=0.029, OR=0.511). Significant risk factors among women with depression were: working woman; 31.8% (p- value=0.000,OR=0.286), domestic  violence;  68.2%  (p-value=0.000,  OR=3.571),  difficult  relationship  with in-laws; 22.7% (p-value=0.000, OR=4.8), sleep disturbance; 54.5% (p-value=0.008, OR=2.0), primigravida; 45.5% (p-value=0.000, OR=17.246) and unplanned pregnancy; 18.2% (p-value=0.000, OR=3.0). Other factors that were found to be significant in the  depression  group  only  were: unsatis- factory relationship with husband; 22.7% (p-value=0.000, OR=4.118),  stressful  life  event  in  previous  year; 45.5% (p-value=0.000, OR=2.167), and tertiary education; 68.2% (p-value=0.002, OR=0.916). Conclusion: Psychosocial and demographic factors such as working woman, domestic violence, and difficult relationship with in-laws and sleep disturbance had a  significant  association  with  antenatal  anxiety and depression. Obstetric risk factors were primigravida and unplanned pregnancy. Significant association with depression was unsatisfactory relationship with husband, stressful  life  event  in  a  previous year and tertiary education.